Ahlaki Kriterler ve Rabbani Alim Hassasiyeti Açısından İlmi Emanet - Mısri, Mahmud (FSM Vakıf Üniversitesi, 2014)
İlmî emanet, telakkî ve edâ yönünden ahlaki kriterlere uymayı kendine prensip edinmiş rabbânî bir alimin en bâriz sıfatlarından birisidir. Telakkîde ilmi fazilet ehlinden almak ve ilmin tahsilinde metot takibi elzemdir. Yine telakkî âdâplarına uymak ve metni yorumlamakta güvenilirlik de vazgeçilmez prensiplerdendir. Bilginin aktarılmasında liyakat, ana kaynağın gösterilmesi, ilmî alıntı kurallarına riayet, muhatabın durumunun dikkate alınması ve ifade güzelliği gibi ilkeler ilmî çalışmaların olmazsa olmaz şartlarındandır.

The reliability may be the most prominent characteristic of the religious scholar who abides by the moral principles in both reception and performance. So, it’s a must that the reception is received from the people of favor, along with committing to the reception disciplines, and the reliability in understanding; on the other hand, it’s a must that the capability is available in performance, in addition to ascribing to references, the trustworthiness in transmission, taking into account the state of the recipient, and the good formulation.
Scientific Reliability: Between the Moral Disciplines and Godliness of the Religious Scholar Scientist
Keywords: Güvenirlilik; İlim; Telakki; Nakil; Alıntı; Scientific Reliability; Reception; Performance; Transmission; Ascribing